HISTORICAL EXPERIENCE OF THE BRITISH ARMED FORCES IN COUNTERING DOMESTIC TERRORISM (Південний архів (історичні науки), 2023)
One of the most important domestic responsibilities of the Armed Forces of the United Kingdom in ensuring the security of the nation is the fight against terrorism within the country. Throughout the twentieth and twenty-first centuries, the United Kingdom has faced various forms of terrorism, including the activities of the Provisional Irish Republican Army (IRA) and international extremist organizations. This research aims to examine historical background, strategies and methods of counter-terrorism in Britain and their relevance for today’s world where terrorism is a growing threat and for Ukraine. The research methods include analysis of official government documents, reports, specialist literature, legal frameworks, media publications; historical analysis, which allows us to consider the development of the role of the Armed Forces in preventing terrorism. The literature analysis shows that while the military involvement in the IRA conflict and its involvement in counter-terrorism as part of international coalitions abroad has been the subject of many studies, the domestic use of the Army remains partly understudied subject. The findings of the study show that the British Armed Forces have developed and adapted their counter-terrorism strategies using a variety of methods, including counter-terrorism operations, public security measures, intelligence and enhanced interagency coordination. It concludes that the experience of the British Army is valuable as a model for countering specific threats to national security that exist in the modern world. This refers in particular to the activities of the russian federation, which since 2014 has used a wide range of terrorist methods in its aggression against Ukraine and also supported the violence escalation to destabilize regional situation in the Middle East and West Asia, provided covert funding and resources to various terrorist groups.
Keywords: Ministry of Defense, armed forces’ domestic role, national security, counterterrorism, international terrorism, Operation Temperer, Operation Banner